Identification and Development of KASP Markers for Novel Mutant BnFAD2 Alleles Associated With Elevated Oleic Acid in Brassica napus - Fu, Ying; Mason, Annaliese S.; Zhang, Yaofeng; Yu, Huasheng (Frontiers in Plant Science, 2021)
The fatty acid desaturase FAD2 genes are the main contributors to oleic acid content, and different FAD2 alleles can result in different oleic acid contents in rapeseed oil. Hence, identification of allelic variation in FAD2 is an extremely desirable breeding goal. By performing QTL mapping using 190 F2:3 lines genotyped by genome-wide single nucleotide polymorphism (SNP) markers assayed by the Brassica 60 K Infinium BeadChip Array, four quantitative trait loci (QTL) for C18:1 content were mapped on chromosomes A01, A05, A09 and C05 over three years in a population segregating for oleic acid content. Two BnFAD2 genes on A05 and C05 were anchored within the QTL intervals, explaining 45 - 52% and 15 - 44% of the observed variation for C18:1 content. Sequence polymorphisms between the corresponding coding regions of the parental lines found two single-nucleotide polymorphisms (SNPs) in BnFAD2.A05 and BnFAD2.C05, respectively, which led to the amino acid changes (C421T and G1073E) in the corresponding proteins. The mutation sites of Bnfad2.A05 and Bnfad2.C05 alleles were located within the second H-box and near the third H-box motif of the protein, respectively, and were found to be novel mutant alleles. Lines resulting from the combination of these two alleles contained up to 88% oleic acid in their seed oil, compared with 63% in wild-type controls. Two competitive allele-specific PCR (KASP) markers based on these two mutation sites were successfully developed and validated in segregating F2 populations. These markers will facilitate breeding for ultra-high seed oleic acid content in oilseed rape.